AB0079 Anti-c5a receptor antibody treatment ameliorates disease activity in delayed-type hypersensitivity (dth) arthritic mice. (23rd January 2014) - Nansen, A.; Atkinson, S. M.; Usher, P.; Haase, C.; Hornum, L.
Abstract : Background: C5a is an anaphylatoxin generated in response to complement activation. C5a promotes leukocyte chemotaxis and activation via the C5a receptor (C5aR), both directly on C5aR-positive cells such as neutrophils, monocytes and macrophages, and indirectly on T cells via effects on C5aR-positive antigen specific cells (APCs) 1 . C5a production and C5aR signalling have been implicated in a wide range of inflammatory disorders including rheumatoid arthritis (RA) 2 . DTH arthritis is a single-paw arthritis model, which is dependent on CD4 + T cells. Besides T cells, neutrophils and macrophages are involved in the pathology, and inflammatory mediators associated with these cells are induced locally in the arthritic paw 3 Objectives: The purpose of this study was to investigate the therapeutic effect of a blocking anti-C5aR antibody in a single–paw arthritis model in mice in both a 2-week multiple-dose (MD) study and in a single-dose (SD) study with read-out at 60 h post-dosing. Methods: DTH arthritis was induced as described by Atkinson 3 . In the MD study mice were treated twice weekly with anti-C5aR antibody (25 mg/kg/dose) from the day of arthritis induction. Mechanistic studies were conducted to investigate the immune-modulating effect of a SD of 25 mg/kg anti-C5aR with read-out at 60 h post-dosing/arthritis induction. Cytokine/chemokine levels in whole–paw homogenate supernatants were analyzed using ELISA and bioplex. Paw sections were evaluated histologically, and composition of leukocyte subsets isolated from lymph nodes and arthritic paws were analyzed by flow cytometry. Statistics: unpaired two-sided t-test. Results: Significant reduction in paw swelling (P<0.01) and histopathology score (P<0.0001) was observed in the MDstudy. Swelling of the arthritic paw was also significantly reduced compared to control–treated mice in the SD study (P<0.0001). Also a single dose of anti-C5aR resulted in significantly reduced levels of MIP-2, MCP-1 and TNFα (P<0.05 for each analyte) in the arthritic paw compared to the levels found in control-treated mice. However, no difference was detected in the total number of leukocytes infiltrating the arthritic paws 60 h after SD treatment. Flow cytometric analysis of leukocyte subsets isolated from arthritic pawsafter SD treatment revealed significant reductions in CD4 + T cell counts of anti-C5aR-treated mice compared to control-treated mice (P<0.05), which correlated with significantly reduced CD4 + T cell proliferation (P<0.05) in the draining popliteal lymph node. Target validation in control-treated DTH arthritic mice revealed expression of C5aR on neutrophils (blood and paw) and on a subset of macrophages (paw), but not on CD4 + T cells. Conclusions: Our studies reveal a significant effect of anti-C5aR treatment on DTH arthritis disease activity, and our mechanistic SD studies strongly suggests that the effect is mediated via reduced local production of inflammatory mediators and reduced CD4 + T cell proliferation, while no effect on leukocyte chemotaxis was observed 60 h after SD anti-C5aR antibody treatment. The effect on CD4 + T cell proliferation is probably indirect via effects of an anti-C5aR antibody on APCs. References: Dunkelberger JR et al.(2010) Mol Immunol 47: 2176–2186; Lee H et al. (2008) Immunol Cell Biol 86: 153–160; Atkinson SA et al. (2012) Arthritis Res Ther 14(3):R134 Disclosure of Interest: A. Nansen Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, S. Atkinson Employee of: PhD student, Research performed at Novo Nordisk A/S, P. Usher Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, C. Haase Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, L. Hornum Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S